2004
DOI: 10.1038/sj.onc.1208079
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between Src family kinases and receptor tyrosine kinases

Abstract: Src family tyrosine kinases (SFKs) are involved in a diverse array of physiological processes, as highlighted in this review. An overview of how SFKs interact with, and participate in signaling from, receptor tyrosine kinases (RTKs) is discussed. And also, how SFKs are activated by RTKs, and how SFKs, in turn, can activate RTKs, as well as how SFKs can promote signaling from growth factor receptors in a number of ways including participation in signaling pathways required for DNA synthesis, control of receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
391
2
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(408 citation statements)
references
References 155 publications
9
391
2
4
Order By: Relevance
“…We describe here that activation of c-Src might be mediated by activation of the EGFR (Figures 5 and 6), Src activation being required for full Akt activation and survival ( Figure 6). Src family tyrosine kinases are activated by tyrosine kinase receptors and, in turn, can promote signalling from growth factor receptors in a number of ways including DNA synthesis, control of receptor turnover, actin cytoskeleton rearrangements, motility and survival (Bromann et al, 2004). There are many reports indicating that c-Src protein expression and/or activity is elevated in epithelial cancers (Biscardi et al, 1999) and activation of c-Src in hepatocellular carcinoma cells is highly correlated with the indices of early-stage phenotype (Ito et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We describe here that activation of c-Src might be mediated by activation of the EGFR (Figures 5 and 6), Src activation being required for full Akt activation and survival ( Figure 6). Src family tyrosine kinases are activated by tyrosine kinase receptors and, in turn, can promote signalling from growth factor receptors in a number of ways including DNA synthesis, control of receptor turnover, actin cytoskeleton rearrangements, motility and survival (Bromann et al, 2004). There are many reports indicating that c-Src protein expression and/or activity is elevated in epithelial cancers (Biscardi et al, 1999) and activation of c-Src in hepatocellular carcinoma cells is highly correlated with the indices of early-stage phenotype (Ito et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression and activation of src-family kinases have been implicated in a number of human malignancies but thus far they have not proven to be effective clinical targets [12][13]. Despite this, molecular studies continue to show src to play a potential role in clinically important pathways in breast cancer including the steroid and peptide hormone signaling pathways [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…17 SFK are thought to interact with a cell surface receptor and participate in initial signal transduction via this receptor. 18 It is reported that several RTK, including c-Fms, PDGF receptor b, c-Kit, and epidermal growth factor receptor (EGFR), activate SFK. 18,19 Also, SFK have been reported to activate STAT pathways and play a role in cytokine-induced cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…18 It is reported that several RTK, including c-Fms, PDGF receptor b, c-Kit, and epidermal growth factor receptor (EGFR), activate SFK. 18,19 Also, SFK have been reported to activate STAT pathways and play a role in cytokine-induced cell proliferation. 20 Originally Lyn was cloned as a signal component of B-cell antigen receptor, but recent studies revealed that Lyn also acted as a signal component of cytokine receptors such as erythropoietin receptor, CSF-1 receptor, and c-Kit, and promoted mitogenic signaling from them.…”
Section: Introductionmentioning
confidence: 99%